The Effectiveness of Using Board Race Game in Teaching Students’ Vocabulary Mastery - Ginting, Melany Apriliana Liasta; Suhartono, Luwandi; Husin, Syarif (British (Jurnal Bahasa dan Sastra Inggris), 2025)
Vocabulary mastery is fundamental to the development of English language proficiency, as it underpins the acquisition of listening, speaking, reading, and writing skills. In Indonesia, many junior high school students face challenges in expanding their vocabulary due to passive and repetitive learning methods. This study examined the effectiveness of the Board Race Game in improving vocabulary mastery, with a focus on nouns and adjectives. A quantitative approach with a pre-experimental design was used, involving 22 seventh-grade students from a junior high school. Data were gathered through a pre-test and post-test, each comprising 20 multiple-choice questions. The results showed a marked improvement in vocabulary scores, with the average increasing from 67.73 to 82.50. Statistical analysis using a paired sample t-test indicated a significant difference, and the effect size was calculated at 1.09, demonstrating a strong effect. These findings suggest that the Board Race Game is an effective tool for enhancing vocabulary learning.